Olefin Hydroarylation via Ni/Co Dual Catalysis - Shevick, Sophie L. (Trends Chem, 2019)
Cobalt/nickel dual-catalysis enables the branch-selective hydroarylation of olefins through a novel “cage-rebound” transmetalation pathway. This process allows for the rapid introduction of complexity by coupling readily available iodoarenes with abundant and unbiased alkenes without the need for substrate prefunctionalization.